Representation of Toxic Relationship in The Web Series “Yang Hilang dalam Cinta” - Fathul Qorib; Modisa Diyah Rahmadani; Moch Rofi’i (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2024)
Yang Hilang dalam Cinta is an Indonesian web series that addresses the issue of toxic relationships. The series describes how bad the effects of a toxic relationship can be for someone, such as what Dara's character experienced, namely physical and verbal violence from her partner. However, many people are still unaware that they are in a toxic relationship. This study aims to find out how the issue of toxic relationships is represented in the web series Yang Hilang dalam Cinta. The research method used is a qualitative research method using Roland Barthes' semiotic analysis technique which uses the terms denotation, connotation and myth. The results of this study indicate that there is a toxic relationship that makes someone feel physically and mentally unsafe for the person in it. Signs of a toxic relationship include physical violence, uncontrolled emotions, dishonesty, possessiveness and excessive jealousy.